(untitled) - Hálková, Klára (Romanica Olomucensia, 2012)
This contrastive analysis examines different infinitive constructions in protasis, their semantic value and their equivalents in Czech language. Using the parallel corpus Intercorp as the main tool we can define Czech equivalents and check if the meanings of the adverbial infinitives agree with the theory.
Keywords: infinitive; contrastive analysis; Spanish; Czech.